Highly Stable Sn─Pb Perovskite Solar Cells Enabled by Phenol-Functionalized Hole Transporting Material - Wu, Jianchang; Hu, Manman; Dai, Qingqing; Alkan, Ecem Aydan; Barabash, Anastasia; Zhang, Jiyun; Liu, Chao; Hauch, Jens A.; Han, Gao Feng; Jiang, Qing; Wang, Tonghui; Seok, Sang Il; et al. (Angewandte Chemie International Edition, 2025)
Sn─Pb perovskites, a most promising low bandgap semiconductor for multi-junction solar cells, are often limited by instability due to the susceptibility of Sn2+ to oxidation. Inspired by the antioxidative properties of polyphenolic compounds, we introduce the reductive phenol group and strong electronegative fluorine into an organic conjugated structure and design a multi-functional polymer with fluorine and phenol units (PF─OH). The design of PF─OH allows the effective rise in the energy barrier of Sn2+ oxidation, leading to a significant enhancement in the stability of Sn─Pb perovskite devices from 200 to 8000 h—an improvement of around 100 times. Additionally, the strong binding energy between Sn2+ and the phenol in PF─OH critically influences Sn─Pb perovskite's crystallization and grain growth, resulting in perovskite films with fewer pinholes at the buried interface and extended carrier lifetimes. This enhancement not only boosts the power conversion efficiency (PCE) to 23.61%, but also significantly improves the operational stability of the devices. Ultimately, this design strategy has been proven universal through the phenolization of a series of molecules, marking a milestone in enhancing the stability of Sn─Pb perovskites.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Alcohol soluble; Hole transporting material; Phenol-functionalized; Sn─Pb perovskite solar cells; Tandem solar cells